Triglyceride Storage Disease: A Disorder of Lipolysis in Adipose Tissue in Two Patients. Issue 5844 (6th January 1973) - Gilbert, C.; Galton, D. J.; Kaye, J.
Abstract : An obese patient was studied whose adipose tissue showed a significant reduction in release of glycerol (P < 0·05) when stimulated by isoprenaline despite normal rises in tissue levels of cyclic-AMP. However, lipolysis was stimulated by a fast of 14 days as judged by weight loss and a rise in plasma fatty acids from 0·4 to 1·2 mM. The defect in this patient may be familial since her obese daughter also showed diminished release of glycerol from adipose tissue on three occasions when stimulated by isoprenaline, despite normal rises in levels of cyclic-AMP.